Do cognitive bias and heuristics influence improvement in knee pain in patients with knee osteoarthritis treated with open label placebo? The CHIPS study - An exploratory study using questionnaire and group concept mapping - Tommy Kok Annfeldt; Elisabeth Ginnerup-Nielsen; Eva Elisabeth Wæhrens; Lene Vase; Lars Erik Kristensen; Tanja Schjødt Jørgensen (Osteoarthritis and Cartilage Open, 2025)
Objective: This study explored if the patient-experience and the affect heuristic influenced improvements in painful symptoms, in response to open label placebo injections in patients with knee OA. It furthermore explored if other cognitive biases or heuristics were involved in the response to open-label placebo. Method: A mixed method study in a pre-specified knee OA cohort. The influence of patient-experience, and the affect heuristic, on change in painful symptoms in response to an open-label placebo injection, were assessed using a questionnaire and multivariate linear regression. The group concept mapping method was used to characterise the expectations and hopes regarding the effect of an open-label placebo injection in non-responders and responders, defined as the lower- and upper quartile of the ΔVAS pain scores. Results: 103 participants received the questionnaire, and 60 finalised questionnaires were included in the analysis showing that the reduction in pain was associated with the patient-experience and that the affect heuristic acted as an effect modifier. Three workshops were held for non-responders (n ​= ​13) and responders (n ​= ​15) each generating respectively 113 and 119 statements. It was found that the two groups reported different expectations and hopes for the open label placebo injections. Conclusions: The patient-experience influenced the response to an open label placebo injection in patients with knee OA, and this influence was moderated by the strength of the affect heuristic. Furthermore, non-responders and responders reported different hopes and expectation towards the open label placebo injection indicating the presence of the optimism bias in the responder group.